EFFECT OF INFLIXIMAB ON DYNAMICS OF FUNCTIONAL CLASS AND RADIOLOGICAL SIGN OF BONE AND CARTILAGINOUS TISSUES ALTERATION OF JOINTS IN PATIENTS WITH DIFFERENT TYPES OF JUVENILE ARTHRITIS - E.I. Alexeeva; A.M. Alekseeva; S.I. Valieva; T.M. Bzarova; R.V. Denisova; G.V. Mikhaleva (Вопросы современной педиатрии, 2008)
An objective of this trial was evaluation of effect of treatment with blocker of tumor necrosis factor infliximab on dynamics of functional class and radiological changes of bone and cartilaginous tissue of joints in children with different clinical types of juvenile arthritis (JA). Infliximab was used according to standard scheme on 0, 2, 6 and then every 8 week by intravenous infusion. Mean single dose of infliximab was 6,8 ± 2,3 mg/kg. All children were treated with immunosuppressive agents (ciclosporin in 6% of patients, methotrexate in 60%, ciclosporin combined with methotrexate — 20%, ciclosporin with leflunomide — 5%, leflunomide with methotreate — 4%) combined with anti cytokine treatment. 7 children were treated with oral glucocorticoids in mean dose 0,37 mg/kg daily. disorders in joint function and structural changes of joints of different severity (radiological sign) were discovered in all patients before starting of treatment with infliximab. Duration of observation was 6 week — 2 years. Authors made a conclusion that treatment with infliximab prevents progressing of bone and cartilaginous destruction in all types of AJ, not depending on intensity of its clinical activity. This medication provides for full functional recovery of joints and elimination of features of disablement in patients with good clinical activity.Key words: children, juvenile arthritis, infliximab, treatment.